Analysis of Labor Informality in Villavicencio – Colombia (2015-2018) (2020)
In this article the socioeconomic profile of the employed population in the informal sector of the municipality of Villavicencio (Colombia) is determined, and for this, the data obtained from the Great Integrated Household Survey GEIH (2015-2018) are used and a probit model is applied. It is concluded that being a woman, having a low level of education, earning low income, being single, working more hours per week, not having a work contract, not having a retiree plan, belonging to the subsidized health regime, increase the probability of being in the informal labor market.